High-Isolation CMOS T/R Switch Design Using a Two-Stage Equivalent Transmission Line Structure - Chenxi Zhao; Yipeng Wu; Huihua Liu; Yunqiu Wu; KAI Kang (IEEE Access)
A fully integrated Ku-band transmit/receive (T/R) switch based on a two-stage equivalent transmission line structure has been designed using a 180-nm complementary metal-oxide-semiconductor (CMOS) process. An analysis shows a relation between the series inductance and turn-on resistance for high isolation. A stack structure with feed-forward capacitors was chosen as a means of improving the power-handling capability of the switch. A low insertion loss (IL) of the switch was achieved by eliminating series transistors. The measured minimum ILs of the switch in the transmitter (TX) and receiver (RX) modes are 2.7 dB and 2.3 dB, respectively. The measured isolations in the TX and RX modes are greater than 34 and 25 dB, respectively, from 15 to 18 GHz. The design reaches a measured input 1-dB power compression point ( $IP_{1}dB$ ) of 22 dBm at 17 GHz. The switch achieves stringent isolation, insertion loss, and power-handling capability requirements along with the capability of full integration, demonstrating its great potential for use in fully integrated CMOS T/R chips.